A liquid chromatography-tandem mass spectrometry assay for the profiling of classical and 11-oxygenated androgens in saliva. (September 2019) - Schiffer, Lina; Adaway, Joanne E; Arlt, Wiebke; Keevil, Brian G
Background: Classical and 11-oxygenated androgens both contribute to the androgen pool. Regular monitoring of the androgen status is required in disorders of steroidogenesis, and multiplexing of androgens improves the diagnostic ability of an assay. Due to the cheap non-invasive collection, saliva is advantageous when multiple samples are required. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) offers sensitive, simultaneous quantification of steroids with short run times. Here, we have developed an LC-MS/MS assay for the simultaneous measurement of 17-hydroxyprogesterone, androstenedione, testosterone, 11β-hydroxyandrostenedione and 11-ketotestosterone in saliva. Methods: Samples (300 μ L unstimulated whole saliva) were prepared by supported liquid extraction with dichloromethane and were reconstituted in 40% methanol. After online solid phase extraction with C18 cartridges, liquid chromatography was performed on a C8 column using a water/methanol gradient containing 0.1% formic acid and 2 mmol/L ammonium acetate. A Waters TQ-S mass spectrometer was used for quantification. Results: Total run time was 6.4 min. For all analytes, recovery was between 89% and 109%, ion suppression between 86% and 105%. Intra- and inter-assay comparisons showed a coefficient of variation <10% and the bias between measured and nominal concentration varied between –8% and 10%. Interference with a large set of natural and synthetic steroids was excluded. The assay was applied for the measurement of the androgen profile in healthy men ( n = 17) and women ( n = 10) which confirmed the sensitivity of the assay to be appropriate. Conclusion: We present a novel LC-MS/MS assay for the comprehensive profiling of classical and 11-oxygenated androgens with potential for routine clinical application.